Drug-Induced Pulmonary Fibrosis: National Database Analysis - Olga I. Butranova; Elizaveta N. Terekhina; Sergey K. Zyryanov; Geliia N. Gildeeva; Anna A. Abramova; Yury O. Kustov; Irina L. Asetskaya; Vitaly A. Polivanov (Biomedicines)
Background/Objectives: Pulmonary fibrosis (PF) results in a progressive decline of lung function due to scarring. Drugs are among the most common causes of PF. The objective of our study was to reveal the structure of drugs involved in PF development. Methods: we performed a retrospective descriptive pharmacoepidemiologic study on spontaneous reports (SRs) with data on PF registered in the Russian National Pharmacovigilance database for the period from 4 January 2019 to 31 May 2024. Results: A total of 1308 SRs on PF were finally identified with patients mean age of 59.3 ± 23.4 years. Death was reported in 30.7% (n = 401) with mean age of 59.9 ± 13.8 years. In the structure of culprit drugs, the following groups were leaders: antineoplastic and immunomodulating agents (51.9%); systemic hormonal preparations, excluding sex hormones and insulins (7.4%); drugs affecting nervous system (7.1%); respiratory system (7.1%); alimentary tract and metabolism (6.5%); and cardiovascular system (5.5%). In the total sample, the top ten drugs were rituximab (5.5%), methotrexate (4.4%), etanercept (4.2%), leflunomide (4.0%), adalimumab (3.7%), tocilizumab (3.3%), abatacept (3.0%), alendronic acid (2.7%), secukinumab (2.6%), and infliximab (2.4%). The number of SRs per year nearly doubled from 2021 to 2022 and from 2022 to 2023 with a maximum peak expected for 2024. Conclusions: Our study demonstrated increased reporting on PF in the National Pharmacovigilance database from 2019 to 2024. We revealed outstanding results for the role of antineoplastic and immunomodulating agents in PF development.